Application of the Local fractional Adomian Decomposition and Series Expansion Methods for Solving Telegraph Equation on Cantor Sets - Jafari, Hossein; Jassim, Hassan Kamil (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, we will compare between the local fractional Adomian decomposition method (LFADM) and local fractional series expansion method (LFSEM) for solving the telegraph equation on Cantor sets within local fractional operator. The results obtained by (LFADM) are compared with the results obtained by (LFSEM). Some examples are given to illustrate the efficiency and accuracy of the presented methods.
Keywords: Fractional telegraph equation Local fractional Adomian decomposition method Local fractional series expansion method Local fractional operators